Urgensi Laboratorium Pendidikan Agama Islam: Studi Kasus Madrasah Aliyah di Kabupaten Cilacap - Kuswantoro Toro; Amri Yahya (Institute of Research and Public Service Universitas Jenderal Soedirman, 2026)
This study is to find out the urgency of the Islamic Religious Education laboratory in Madrasah Aliyah, especially in the development of knowledge and in religious practice activities, so that in learning Islamic Religious Education in the laboratory, students have experience in the actualization of Islamic Religious Education. This research method is a qualitative study by conducting observations and interviews with the head of the Madrasah and also the Head of the Laboratory to determine the condition of the Islamic Religious Education laboratory in Madrasah Aliyah in Cilacap Regency. The results of the study are still many Madrasah Aliyah that do not have an Islamic Religious Education laboratory in Cilacap Regency. So that in the implementation of Islamic Religious Education practices, it is not carried out in the laboratory but more theory in class and practice of fiqh worship in the mosque or prayer room near the madrasah. The implication is that Madrasah Aliyah is an Educational Institution that focuses on Islamic Religious Education competency, it is time to have an Islamic Religious Education laboratory such as the Al-Quran Laboratory, Hadith Laboratory, Fiqh Worship Laboratory, Islamic Science Laboratory, Multimedia Da'wah Laboratory, and so on. To bridge the gap between theoretical learning in class and practice. So as to form a generation of Muslims who are able to understand and practice Islamic teachings well.